Interfacial Engineering Strategy for High-Performance Zn Metal Anodes - Bin Li (SpringerOpen, 2021)
Abstract Due to their high safety and low cost, rechargeable aqueous Zn-ion batteries (RAZIBs) have been receiving increased attention and are expected to be the next generation of energy storage systems. However, metal Zn anodes exhibit a limited-service life and inferior reversibility owing to the issues of Zn dendrites and side reactions, which severely hinder the further development of RAZIBs. Researchers have attempted to design high-performance Zn anodes by interfacial engineering, including surface modification and the addition of electrolyte additives, to stabilize Zn anodes. The purpose is to achieve uniform Zn nucleation and flat Zn deposition by regulating the deposition behavior of Zn ions, which effectively improves the cycling stability of the Zn anode. This review comprehensively summarizes the reaction mechanisms of interfacial modification for inhibiting the growth of Zn dendrites and the occurrence of side reactions. In addition, the research progress of interfacial engineering strategies for RAZIBs is summarized and classified. Finally, prospects and suggestions are provided for the design of highly reversible Zn anodes.